Assessment of the Relationship Between Pisotriquetral Joint Effusion on Magnetic Resonance Imaging and Wrist Disorders - Johari, Mohammad Sadegh; Moradi, Hamid; Azimi Aval, Mohammad Reza; Abbasi, Zahra; Mirzaei, Mehdi; Mowlahoveyzeh, Shorough (Novelty in Biomedicine, 2026)
Background: The pisiform is a bone that is sometimes considered a sesamoid bone. Pain and tenderness can be due to tendinopathy at the attachment site of the flexor ulnaris tendon, carpal fractures, or osteoarthritis of the pisotriquetral joint. There are limited studies on the association between wrist disorders and pisotriquetral joint effusion; therefore, this study aimed to investigate this association on magnetic resonance imaging (MRI). Materials and Methods: In this cross-sectional study, which investigated the relationship between wrist disorders and pisotriquetral joint effusion on MRI, all patients referred to the radiology department of Besat Hospital in 2024 for wrist disorders underwent MRI. MRI findings included osteoarthritis of the wrist joints, ganglion cysts, dislocations, subluxations, and osteonecrosis. If there were no positive findings, the MRI was considered normal. The significance level was considered less than 0.05. Results: Ninety-three patients were assessed. Fifty-seven patients (61.3%) had pisotriquetral joint effusion, and 36 (38.7%) patients did not have pisotriquetral joint effusion. Joint effusion was not associated with age or gender (P-values > 0.05). Also, there was no association between pisotriquetral joint effusion and the occurrence of osteonecrosis, osteoarthritis, subluxation, dislocation, and ganglion cyst (all P-values > 0.05). Conclusion: There was no association between wrist disorders and pisotriquetral joint effusion.